College Is Not a Restaurant: Challenging Cultural Hegemony in the US Classroom. (June 2014) - Kittler, Juraj
Abstract : In the post 9/11 world, a nonnative US teacher who attempts to challenge existing cultural assumptions may easily trigger hostility and suspicion in the classroom. This chapter conveys the experience of a college professor whose approach often deliberately crosses that line.